Research on the Dilemma of the Adoption Behavior of Network Health Information among Migrant Female Workers in the Perspective of Social Support Theory - Wang, Luyao (Journal of Social Science and Humanities, 2025)
Objective: Migrant female workers who work as vulnerable groups in society w have relatively insufficient social support and attention, and their ability to judge online health information is still lacking. Studying the current status and challenges of adopting online health information among migrant female workers is aimed at improving their information processing capabilities and providing reference for better coping with information overload. Methods: From December 2023 to April 2024, interviews were conducted with 17 migrant female workers from a motor factory in Shanghai, and the interview data were analyzed using the grounded theory research method. Results: After three levels of coding, 36 initial concepts, 15 subcategories, and 5 main categories were finally formed, and a behavioral dilemma model for the adoption of network health information by migrant female workers was constructed based on this. Conclusion: As a socially disadvantaged group, migrant female workers face a severe health situation. However, social factors, personal factors, information perception, information factors, and social support are important factors that affect their adoption of network health information. Social support attempts to help them cope with information dilemmas through various means, and these forms of support are of great significance in improving their adoption of network health information and coping with information overload.